Allergy Test: Seasonal Allergens and Performance in School - Dave E. Marcotte (Institute for the Study of Labor (IZA), 2014)
Seasonal pollen allergies affect approximately 1 in 5 school age children. Clinical research has established that these allergies result in large and consistent decrements in cognitive functioning, problem solving ability and speed, focus and energy. However, the impact of seasonal allergies on achievement in schools has received no attention at all from economists. Here, I use data on daily pollen counts merged with school district data to assess whether variation in the airborne pollen that induces seasonal allergies is associated with performance on state reading and math assessments. I find substantial and robust effects: A one standard deviation in ambient pollen levels reduces the percent of 3rd graders passing ELA assessments by between 0.2 and 0.3 standard deviations, and math assessments by between about 0.3 and 0.4 standard deviations. I discuss the empirical limitations as well as policy implications of this reduced-form estimate of pollen levels in a community setting.
Keywords: I10; I20; I21; 330; education; health; air quality